Multimode coordinated multipoint transmission with nonideal timing synchronization - qi GUZhe; pei ZHANGZhong (Tongxin xuebao)
Against the negative impact of non-ideal timing synchronization on the coordinated multipoint (CoMP) trans-mission, a multimode algorithm was proposed. According to the average achievable rates of the different CoMP transmis-sion modes under non-ideal timing synchronization condition, such as coordinated beamforming (CB) and joint processing (JP), the mode selection variable and the mode selection threshold were acquired. In the multimode algorithm for CoMP transmission, user equipments (UE) estimate the timing synchronization errors, calculate the mode election va-riables and the mode selection thresholds firstly. After rds, UEs select the CoMP transmission mode, feedback the se-lection results to coordinated base stations (BS). Finall , According to the feedback from UEs, coordinated BSs switch the CoMP transmission mode between CB and JP adaptively to maximize the average achievable rate. Simulation results show that the multimode algorithm adopt JP to maintain spatial multiplexing gain when timing synchronization errors are small, adopt CB to avoid extra interference between UEs when timing synchronization errors are large. Therefore under, non-ideal timing synchronization condition the proposed multimode algorithm outperforms the traditional algorithms, which only adopt CB or JP for CoMP transmission.